Wearable system for real-time monitoring of hemodynamic parameters: Implementation and evaluation. (May 2020) - Girčys, Rolandas; Kazanavičius, Egidijus; Maskeliūnas, Rytis; Damaševičius, Robertas; Woźniak, Marcin
Highlights: A novel noise-resistant photoplethysmographic signal input subsystem based on monitoring of Arterial Pulse Wave front edge modulated with an optical Barker code. Using only 20 % of energy for hemodynamic parameter monitoring in comparison to conventional methods. Accuracy of the developed device meets the grade A requirements according to the BHS standard. Abstract: Cardiovascular diseases are the leading cause of mortality in the world. The development of new devices and methods for continuous monitoring of hemodynamic parameters throughout the day is relevant for ensuring healthy lifestyle as well as for supporting the ageing population. We describe the Wearable Hemodynamic Parameter Monitoring System for continuous 24/7 hemodynamic parameter monitoring. The proposed solution uses a novel noise-resistant photoplethysmographic (PPG) signal input subsystem based on monitoring of Arterial Pulse Wave front edge modulated with an optical Barker code. The developed system uses only 20 % of the energy for hemodynamic parameter monitoring in comparison to conventional methods. The developed system ensures the same quality of blood pressure measurement as top products in the market, but energy saving allows the prolonged use of device in home environment.